Accuracy of multichannel intraluminal impedance and pH testing for detection of gastro-oesophageal reflux (GOR) in anaesthetised dogs - Zeiler, Gareth Edward (University of Pretoria, 2024)
Dissertation (MMedVet (Anaesthesiology))--University of Pretoria, 2023.